2020
DOI: 10.26773/smj.201008
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Health and Fitness Competencies of Students in the Process of Physical Education

Abstract: The technology of forming the health and fitness competencies of students of higher educational institutions is reviewed in the present paper, which includes designing the highly efficient educational activity of students and the management activity of a teacher with the principal orientation to the content and forms of the educational process in the personal-development technologies of training. The study aims to substantiate, implement, and verify the efficiency of the original methodical system of physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…The results of our research complement the findings of many scientists [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and expand them.…”
Section: Discussionsupporting
confidence: 86%
“…The results of our research complement the findings of many scientists [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and expand them.…”
Section: Discussionsupporting
confidence: 86%
“…The effectiveness of physical training in the formation of the necessary qualities of specialists depends on the variety of means used, their scope and direction. The studies [5,7] showed the need for integrated use of various means of physical education to optimize the physical well-being of servicemen, whose activities take place in conditions of limited motor performance. The peculiarity of the organization of physical education of servicemen, whose activities have a pronounced hypodynamic nature, is the use of general physical training means with the predominant use of strength and endurance exercises.…”
Section: Resultsmentioning
confidence: 99%
“…The works [1][2][3][4][5] point out a deterioration of the state of health and the level of physical fitness of the male population of Ukraine in recent years under conditions of social, economic and political instability: the rate of depopulation in Ukraine ranks the 2 nd place in the world, the 1-2 nd place in Europe for mortality from cardiovascular diseases; the average life expectancy of men in Ukraine is 10-12 years lower than in the European Union countries; more than 70 % of the adult male population have low and below average levels of physical health. The probability of death of working age men is 38.4 %, which is one of the worst indicators among the civilized countries of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the psychological and pedagogical aspects of the formation of students' to health, scientists [6,7] have developed criteria that are characteristics of their components, namely: the orientation of health needs, the ability to assess personal psychophysical qualities, the skills in operating specific health tools, and the creative approach to the choice of the physical activity forms. The orientation to the health values of students is formed taking into account the following psychological and pedagogical conditions: the orientation of students to the reproduction and development of valeological values; strengthening health functions in the areas of education and leisure of students; the creative attitude to the use of modern approaches in valeological and vocational education; the intensification of the development, expansion, and enrichment of the orientations of future specialists, including them in creative physical fitness and health activities [8,9].…”
Section: Introductionmentioning
confidence: 99%